2017
DOI: 10.4049/jimmunol.1601722
|View full text |Cite
|
Sign up to set email alerts
|

The Granulocyte Progenitor Stage Is a Key Target of IRF8-Mediated Regulation of Myeloid-Derived Suppressor Cell Production

Abstract: Alterations in myelopoiesis are common across various tumor types, resulting in immature populations termed myeloid-derived suppressor cells (MDSCs). MDSC burden correlates with poorer clinical outcomes, credited to their ability to suppress antitumor immunity. MDSCs consist of two major subsets, monocytic and polymorphonuclear (PMN). Intriguingly, the latter subset predominates in many patients and tumor models, though the mechanisms favoring PMN-MDSC responses remain poorly understood. Ordinarily, lineage-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 50 publications
5
70
0
Order By: Relevance
“…The role of the immune-suppressive myeloid compartment in favoring progression of disease in MM has been demonstrated both in experimental 35,36,55,56 and clinical models [57][58][59][60][61] , however this is the first study reporting changes in human HDNs during an hematological malignancy, developed in the bone marrow, where the tumor cells share the same site with myeloid progenitors. Our findings clearly indicate that the combination of phenotypic changes (increased CD64 and Arg-1) and function (reduced phagocytosis and increased immune-suppression) occurring in MM-HDN overlap with those described for G-MDSC in MM, in line with recent reports in the field 62 , while HDN in healthy subjects do not have immunosuppressive features. Key MDSC genes and canonical signaling pathways are activated along tumor progression, as recently demonstrated in murine cancer models, where a consensus set of 817 genes, involved in myeloid cell recruitment and angiogenesis, was identified 63 .…”
Section: Discussionsupporting
confidence: 90%
“…The role of the immune-suppressive myeloid compartment in favoring progression of disease in MM has been demonstrated both in experimental 35,36,55,56 and clinical models [57][58][59][60][61] , however this is the first study reporting changes in human HDNs during an hematological malignancy, developed in the bone marrow, where the tumor cells share the same site with myeloid progenitors. Our findings clearly indicate that the combination of phenotypic changes (increased CD64 and Arg-1) and function (reduced phagocytosis and increased immune-suppression) occurring in MM-HDN overlap with those described for G-MDSC in MM, in line with recent reports in the field 62 , while HDN in healthy subjects do not have immunosuppressive features. Key MDSC genes and canonical signaling pathways are activated along tumor progression, as recently demonstrated in murine cancer models, where a consensus set of 817 genes, involved in myeloid cell recruitment and angiogenesis, was identified 63 .…”
Section: Discussionsupporting
confidence: 90%
“…IRF8 regulates myeloid cell differentiation through repressing granulocyte development and promoting differentiation of monocytic cells such as dendritic cells and macrophages (39)(40)(41)(42)(43). IRF8 functions in hematopoietic cell differentiation and activation have since been extended to other hematopoietic cells, including B, NK, and T cells (25,31,41,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). However, IRF8 functions in T cells are apparently tissue-and disease-specific (25,30,38,46,53,57).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced cancer is associated with a myeloid bias characterized by increased frequencies of circulating granulocyte-monocyte progenitors that are skewed toward differentiating into granulocytes (21). Tumor-derived factors, such as G-CSF, GM-CSF, and IL-6, drive this myeloid bias (22) and result in a circulating and tumor-infiltrating MDSC population that accelerates tumor progression by suppressing T cell responses and releasing factors that promote metastasis. Cui et al (23) found that MDSC in EOC triggered acquisition of stem cell-like features in cancer cells and increased metastatic potential, and they found that myeloid cell (CD33 + ) accumulation was associated with worse outcomes.…”
Section: Introductionmentioning
confidence: 99%